Reproduction as Genealogy in Anna Torma’s Textile Art - Kirsty BELL (E-REA)
Various concepts and practices of reproduction are central to the work of Canadian embroidery artist Anna Torma, even when the artist’s materials and techniques impede manual, mechanical, or digital reproduction of the work itself. Reproduction is at once a creative act, a literal and metaphorical genealogy, and a biological imperative; it becomes a sort of guiding principle in Torma’s embroideries. Through her use of art works created by others and through the recurring themes of biology and evolution, Torma creates artistic and familial genealogies that demonstrate new ways of thinking about reproduction in/of textile art.